Shared genetic variants between serum levels of high-density lipoprotein cholesterol and wheezing in a cohort of children from Cyprus - Yiallouros, Panayiotis K.; Kouis, Panayiotis; Kolokotroni, Ourania; Youhanna, Sonia C.; Savva, Savvas C.; Dima, Kleanthi; Zerva, Aikaterini; Platt, Danielle; Middleton, Nicos; Zalloua, Pierre (My University, 2016)
Background: In a cohort of children in Cyprus, we recently reported low levels of high density lipoprotein cholesterol (HDL-C) to be associated with asthma. We examined whether genetic polymorphisms that were previously linked individually to asthma, obesity, or HDL-C are associated with both asthma and HDL-C levels in the Cyprus cohort. Methods: We assessed genotypes frequencies in current-wheezers (n = 190) and non-asthmatic controls (n = 671) and HDL-C levels across several genotypes. Binary logistic regression models were used to assess the effect of genotypes on wheezing risk and examined whether this effect is carried out through changes of HDL-C. Results: Of the 16 polymorphisms tested, two polymorphisms TNFa rs3093664 and PRKCA rs9892651 presented significant differences in genotype distribution among current-wheezers and controls. Higher HDL-C levels were noted in carriers of genotype GG of polymorphism TNFa rs3093664 that was protective for wheezing Vs AG and AA genotypes (65.3 Vs 51.8 and 53.3 mg/dl, p-value < 0.001 and p-value for trend = 0.028). In polymorphism PRKCA rs9892651, HDL-C levels were lower in carriers of CC and TC genotypes that were more frequent in current-wheezers Vs TT genotype (52.2 and 52.7 Vs 55.2 mg/dl, p-value = 0.042 and p-value for trend = 0.02). The association of TNFa rs3093664 with wheezing is partly mediated by its effect on HDL-C whereas association of PRKCA rs9892651 with wheezing appeared to be independent of HDL-C. Conclusions: We found evidence that two SNPs located in different genetic loci, are associated with both wheezing and HDL-C levels, although more studies in other populations are needed to confirm our results.
Keywords: Asthma; Children; Genotypes; High density lipoprotein cholesterol; Polymorphisms